Assessment of quality of life and self-esteem of individuals with chronic venous diseases (Research, Society and Development, 2024)
Objective: To evaluate the quality of life and self-esteem of adults and elderly people with chronic venous disease. Methodology: Observational, descriptive, analytical, cross-sectional and quantitative study. The research was carried out in a philanthropic hospital and in the specialized laboratories Corpore Sano at UNICAP, both located in Recife. In data collection, a socio-clinical-demographic questionnaire, CIVIQ-20 questionnaire and the Rosenberg scale were used. Results: The sample consisted of 23 participants, 69.6% between 41 and 60 years old, 87.0% were female, 43.5% had completed high school. 56.5% had comorbidities and of these, 92.3% had hypertension. We highlight that 47.8% were diagnosed with the disease no more than 5 years ago, 82.6% had both sides of the lower limbs affected, 47.8% with CEAP C2 classification. Regarding the QOL score (CIVIQ-20), the average was 39.5 ± 24.1, the Rosenberg EA score, we found that 43.5 have high EA and 56.5% have medium EA. Conclusion: Given the results, it was observed that individuals with CVD have a medium and high level of EA. Regarding QoL, patients presented an average QoL.